Lantana camara plant extract catalyzed biosynthesis of graphene-metal nanocomposites with potential cytotoxic activities - Kfait Ullah Khan; Misbahur Rehman; Mariam Hameed; Khyzar Hayat; Farhan Saeed; Muhammad Afzaal; Noor Akram; Faiyaz Ahmed; Aasma Asghar; Gebremichael Gebremedhin Hailu (PLoS ONE, 2025)
This study investigates the synthesis and characterization of Plant-Ag-graphene nanocomposites through a combination of spectroscopic and microscopic techniques, the nanocomposites were formed by catalyzing silver nanoparticles with plant extracts, and the resulting structures were analyzed using advanced instrumentation. In the FTIR analysis, distinctive peaks were observed at 3340 cm⁻1 (O-H stretching), 1740 cm⁻1 (C = O stretching), and 1050 cm⁻1. When compared to silver nanoparticles, the nanocomposites exhibited altered peak intensities, indicating modifications in chemical bonding. SEM images revealed that in nanocomposites, nanoparticles were adhered to graphene sheets, confirming the successful formation of Plant-Ag-graphene structures. EDX spectra showed a reduction in the silver content, confirming the integration of graphene into the nanocomposites. XRD analysis confirmed the presence of face-centered cubic-shaped Ag metal in the nanocomposites, while graphene exhibited a hexagonal crystalline shape. UV-Vis spectroscopy demonstrated shifts in peak positions, Spectrum A (400 to 700 nm) and spectrum B (265 nm), suggesting the successful synthesis of Plant-Ag-graphene nanocomposites. Moreover, the cytotoxic activity showed cell inhibition among Plant-Ag-Graphene (65.69%) and Plant-Ag (61.39%), respectively.